Humanisme dalam Sastra Anak: Analisis Nilai Empati dan Persahabatan pada Karya Andrea Hirata - Nurjaman, Ahmad; Puspitasari, Indah; Sari, Raras Hafiidha (UIR Press, 2025)
This study examines the values of empathy and friendship in Andrea Hirata’s children’s literary works, particularly Laskar Pelangi and Ayah, and their relevance to children’s character development. Children’s literature serves as an educational medium that instills moral and social values through relatable stories. The study employs a qualitative descriptive method with content analysis. Data representing empathy and friendship values were analyzed using the empathy theory (Eisenberg & Strayer, 1990) and children’s social development theory (Santrock, 2018). The results show that Andrea Hirata’s works are rich in empathy and friendship values reflected in the characters Ikal, Lintang, Mahar, and Sabari. These values promote social awareness, solidarity, and humanity, aligning with Lickona’s (2014) concept of character education. Andrea Hirata’s works not only possess aesthetic value but also serve as effective learning materials for character-based Indonesian language education.